Effect of flush existence, NAA and GA application on cocoa pod development - Y.T.M. Astuti; Adi Prawoto; Kumala Dewi (Indonesian Coffee and Cocoa Research Institute, 2011)
This experiment was carried out to study the photosynthate allocation between flush and young pods, and the effect of (naphthalene acetic acid) and (gibberellic acid) application to sink strength. Two cocoa clones KW 163 and KW 165 located in Kaliwining Experimental Station of Indonesian Coffea and Cocoa Research Institut were used on this experiment. Each clone was treated with flushes and without flush. Beside that, the young pods sprayed with NAA 250 mg L-1, GA 250 mg L-1, NAA 250 mg L-1 dan GA 250 mg L-1 and control (K = without NAA and GA). There were 2 x 4 treatment combinations for each clone, and replicated three trees for each combination. The parameter were cherelle wilt percentage, sucrose content, fresh and dry weight, long and diameter of healthy and wilting pods.The result showed that sink strength of young pods was lower than that of flushes, which caused application photosynthate translocation to the young pods was lower. NAA and GA application to the pods could improve sucrose allocation, increased pod weight and cherelle wilt was suppressed. The lack of photosynthate on young pod cause metabolism change, so pod became cherelle wilt. But, there was still not known the optimum concentration and method of application of those growth regulators to obtained minimum cherelle wilt.Key words: Cocoa, flush, pod, naphthylacatic acid, gibberellic acid, cherelle wilt.